Systemic Steroid Versus Combined Systemic and Intratympanic Steroid Treatment for Sudden Sensorineural Hearing Loss - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2013)
Objective: The aim of this study was to evaluate the effectiveness of oral steroid treatment versus combined oral and intratympanic dexamethasone injection for idiopathic sudden sensorineural hearing loss. Methods: This was a retrospective case review in which 30 patients in the oral steroid group and 39 patients in the combined oral and intratympanic steroid injection group were compared. Results: The comparison of the initial pure tone audiometry (PTA) threshold results revealed a significant difference between the systemic steroid (SS) group and the systemic and intratympanic steroid group. The initial PTA was 74.33 +/- 22.64 dB (mean +/- SD) in the SS group and 87.49 +/- 26.22 dB (mean T SD) in the intratympanic steroid group. The difference in the initial PTA results was statistically significant between the SS group and intratympanic steroid group (P < 0.05, P = 0.032). The pure-tone gain in the SS group was 20.97 +/- 27.47 dB (mean +/- SD), and that of the group treated with both systemic and intratympanic steroids was 19.36 +/- 22.16 dB (mean +/- SD) (P = 0.49). Conclusions: The results of this study indicate that, in sudden sensorineural hearing loss, the administration of intratympanic steroids in conjunction with SS therapy appears to have the same effect on the restoration of hearing as the effect obtained using SS therapy alone.
Keywords: Sudden hearing loss; systemic steroids; intratympanic delivery; THERAPY; DEXAMETHASONE; METHYLPREDNISOLONE